Inside Southwark Cathedral: a study in psychological-type profiling - Lankshear, David W. (Mental health, religion & culture, 2015)
A series of recent studies have begun to map the psychological-type profile of Anglican churchgoers in England and Wales. This study sets the profile of 120 men and 161 women attending Sunday services in Southwark Cathedral against the profile of 1169 men and 2135 women attending Anglican parish churches. These data found a significantly higher proportion of intuitive types and thinking types within the cathedral congregation and a significantly lower proportion of participants displaying the SJ temperament. The implications of these findings are discussed for appreciating the distinctive style of cathedral worship and of cathedral ministry.